Basil (Ocimum basilicum L.) water needs calculated from the crop coefficient (2017)
The determination of the crop coefficient (Kc) throughout the phenological stages is important for the calculation of water requirements of plants. This study determined the Kc curve for Basil (Ocimum basilicum L.) in Candelaria, Valle del Cauca, and evaluated this Kc in greenhouse conditions. Three drainage lysimeters and a portable meteorological station were used to determine the reference evapotranspiration (ETo), which were set up randomly in an experimental plot. The field capacity (FC) moisture content was determined, and the soil moisture and drainage depth were periodically monitored. Daily water balance calculations were conducted to determine the crop’s water needs (ETc), and the Kc was calculated based on the quotient between ETc and ETo by performing statistical regression analysis. In the second experiment, in a completely randomized bifactorial design, four treatments were established in Cali (Valle). These treatments were amount of water necessary to maintain the soil moisture at FC and amount of water calculated with the Kc (72 % FC), both treatments with and without fertilizers application. The results showed that the Kc values for basil are: growth stage, 0,45 ± 0,02 (25 days after transplant, dat); maturity stage, 0,59 ± 0,02 (26 – 50 dat); and senescence stage, 0,42 ± 0,03 (51 – 71 dat). In greenhouse conditions, dry mass percentage, plant height, soil pH and electrical conductivity were similar for both water regimens. The reduction on water with Kc increased the nitrogen foliar but the water use efficient decreased.